2008
DOI: 10.1002/hipo.20471
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cholinergic status in hippocampus produces spatial memory deficits when combined with kainic acid induced seizures

Abstract: Alzheimer's disease is the most common form of dementia in North America today. Though many risk factors have been suggested to increase the likelihood of developing this disease, an accurate etiology has yet to be described. One of these risk factors commonly associated with Alzheimer's disease is the loss of cholinergic neurons of the medial septum that project to the hippocampus, leading to depletion in cholinergic activity. A second risk factor is the presence of seizures, which can increase the risk of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Cholinergic neurotransmission is known to regulate synaptic plasticity and to play a role in memory behavior [17,43,44]. In line, cholinergic depletion decreases adult neurogenesis [45] and increases the vulnerability of hippocampal neurons to insult thereby contributing to the appearance of hippocampaldependent spatial memory deficits [46,47]. It is thus reasonable to propose that the cholinergic neuronal loss observed in the THY-Tau22 model may emphasize the hippocampal dysfunction primarily caused by tau pathology and contributes significantly to the observed cognitive impairments.…”
Section: Discussionmentioning
confidence: 98%
“…Cholinergic neurotransmission is known to regulate synaptic plasticity and to play a role in memory behavior [17,43,44]. In line, cholinergic depletion decreases adult neurogenesis [45] and increases the vulnerability of hippocampal neurons to insult thereby contributing to the appearance of hippocampaldependent spatial memory deficits [46,47]. It is thus reasonable to propose that the cholinergic neuronal loss observed in the THY-Tau22 model may emphasize the hippocampal dysfunction primarily caused by tau pathology and contributes significantly to the observed cognitive impairments.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, we found that long-term voluntary exercise prevented the loss of ChAT immunoreactive neurons observed in the medial septum of THY-Tau22 mice. Cholinergic neurotransmission promotes hippocampal synaptic plasticity (Doralp and Leung, 2008;Ji and Dani, 2000;Ovsepian et al, 2004), and the depletion of medial septal cholinergic neurons increases the vulnerability of hippocampal neurons to insult and favors the appearance of hippocampus-dependent spatial memory deficits (Craig et al, 2008;Jolkkonen et al, 1997). Thus, it is reasonable to suggest that the prevention of cholinergic alterations by exercise contributes to the impact of exercise on memory performance in THY-Tau22 model.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with bilaterally specific lesion of hippocampus dorsal CA1 and ventral CA3 subregions, KA induced deficits in acquisition of the water maze task and significant memory impairment of the passive avoidance task, suggesting effects on spatial memory and associative memory [17]. In other study, it has been shown that reduced cholinergic status in hippocampus produced spatial memory deficits of rats in water maze task when combined with KA induced seizure [18]. Intrahippocampal injection of KA in rats induced impaired acquisition and retention of visual-spatial information in water-maze task, suggesting spatial cognitive alterations [19].…”
Section: Introductionmentioning
confidence: 81%